Analisis Kinerja Tenaga Kesehatan di RS. Pertamina Bintang Amin - Dewi Setiawati; Samino Samino; Riyanti Riyanti (Universitas Malahayati, 2026)
ABSTRACT The poor performance of health workers in providing services is often associated with low service quality. When an employee carries out his duties and responsibilities, the quality and quantity of performance achieved can be seen, therefore good employee performance will have a direct impact on institutional performance. The purpose of this research is to find out the performance analysis of health workers in hospitals Pertamina Bintang Amin. This type of quantitative research with a cross sectional approach. The research population is all permanent employees of hospital health workers. Pertamina Bintang Amin consisting of doctors, nurses, midwives and other medical personnel as many as 148 respondents. Samples that meet the requirements in this study are 148 respondents. The research instrument is a questionnaire. Data analysis using smartPLS SEM (Partial Least Square – Structural Equation Modeling) Software. This study found that there was an influence of organizational culture with Path Coefficient 0.243 t statistic 1.683, there was an influence of leadership with Path Coefficient 0.520 t statistic 2.828, there was no effect of compensation with Path Coefficient 0.071 t statistic 0.681 on performance, there was an influence of organizational culture in hospital through motivation with a value of 1.73440, there was an effect of work compensation through motivation with a value of 0.6106, there was an effect of supervision through motivation with a value of 1.660 86 health workers in the hospital. Suggestions from this research, can pay attention to and improve the level of performance, pay attention to aspects that can affect the level of employee performance. Keywords: Performance, Health Workers, Hospital Pertamina Bintang Amin. ABSTRAK Buruknya kinerja petugas kesehatan dalam memberikan pelayanan seringkali dikaitkan sdengan rendahnya kualitas pelayanan. Ketika seorang karyawan melakukan tugas dan tanggung jawabnya, maka kualitas dan kuantitas kinerja yang dicapai dapat terlihat maka dari itu kinerja karyawan yang baik akan berdampak langsung pada kinerja institusional. Tujuan penelitian Untuk Mengetahaui Analisis Kinerja Tenaga Kesehatan di RS. Pertamina Bintang Amin. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian s semua pegawai tetap tenaga kesehatan RS. Pertamina Bintang Amin yang terdiri atas tenaga dokter, perawat, bidan, dan tenaga medis lainnya sebanyak 148 responden. Sampel yang memenuhi syarat dalam penelitian 148 responden. Instrumen penelitian adalah kuesioner. Analisa data menggunakan Software smartPLS SEM (Partial Least Square – Structural Equation Modeling). Penelitian ini didapatkan ada pengaruh budaya organisasi dengan Path Coefficient 0,243 t statistik 1,683, ada pengaruh kepemimpinan dengan Path Coefficient 0,520 t statistik 2,828, tidak ada pengaruh kompensasi dengan pathCoefficient 0,071 t statistik 0,681 terhadap kinerja, ada pengaruh budaya organisasi RS berpengaruh melalui motivasi dengan nilai 1,73440, ada pengaruh kompensasi kerja melalui motivasi dengan nilai 0,6106, ada pengaruh supervisi melalui motivasi dengan nilai 1,66086 tenaga kesehatan di RS. Pertamina Bintang Amin. Saran dari penelitian ini, dapat memperhatikan dan meningkatkan tingkat kinerja, memperhatikan aspek-aspek yang dapat memepengaruhi tingkat kinerja pegawai. Kata Kunci: Kinerja, Tenaga Kesehatan, RS. Pertamina Bintang Amin.